2015
DOI: 10.1016/j.jmb.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Segment-Facilitated Dissociation of Fis and NHP6A from DNA Detected via Single-Molecule Mechanical Response

Abstract: The rate of dissociation of a DNA-protein complex is often considered to be a property of that complex, without dependence on other nearby molecules in solution. We study the kinetics of dissociation of the abundant E. coli nucleoid protein Fis from DNA, using a single-molecule mechanics assay. The rate of Fis dissociation from DNA is strongly dependent on the solution concentration of DNA. The off-rate (koff) of Fis from DNA shows an initially linear dependence on solution DNA concentration, characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(113 citation statements)
references
References 49 publications
11
99
0
Order By: Relevance
“…However, the off-rate obtained is within the range reported for DNA-antibody or DNA-protein interactions, for example, the k off of D17.4 DNA aptamer/IgE complex was calculated to be (2.92 ± 0.18) × 10 −3 s −1 or (2.85 ± 0.14) × 10 −3 s −1 depending on the environmental conditions [57, 58]. Giuntoli et al [59] showed that the rate of dissociation from DNA of the Escherichia coli nucleoid protein Fis was approximately k off ~ 8 × 10 −3 s −1 .…”
Section: Discussionsupporting
confidence: 55%
“…However, the off-rate obtained is within the range reported for DNA-antibody or DNA-protein interactions, for example, the k off of D17.4 DNA aptamer/IgE complex was calculated to be (2.92 ± 0.18) × 10 −3 s −1 or (2.85 ± 0.14) × 10 −3 s −1 depending on the environmental conditions [57, 58]. Giuntoli et al [59] showed that the rate of dissociation from DNA of the Escherichia coli nucleoid protein Fis was approximately k off ~ 8 × 10 −3 s −1 .…”
Section: Discussionsupporting
confidence: 55%
“…3 at low salt concentrations are larger due to the computational cost of producing data when the electrostatic interactions are stronger. In experiments where protein unbinding from single binding sites was studied, a high concentration of free ligands (proteins) weakened the salt-dependence of the offrates [20,22,27]. In our simulations, we also investigated the effects of the electrostatic scheme on FD by introducing a fixed concentration of unbound ligands in the solution (see Fig.…”
Section: A Spontaneous Dissociationmentioning
confidence: 99%
“…Besides univalent salt ions, an excess amount of free ligands in solution can also facilitate dissociation of a bound ligand by decreasing the lifetime of the ligand on the binding site [19][20][21][22][23][24][25][26][27]. The free ligands can be identical to the initially bound ligand [21,22,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Dissociation can be facilitated not only by the Fis molecule itself but also by the action of the bacterial protein HU, the yeast HMGB protein NHP6A, 6 as well as other DNA segments. 7 Facilitated dissociation has been observed experimentally for a wide variety of genetic systems, including DNA polymerase exchange in phage T7 replisome during DNA replication, 8 dissociation of metal-dependent transcription factor CueR by apo-CueR, 9 and the facilitated dissociation of eukaryotic High-Mobility Group B (HMGB) protein by itself. 10 In addition, facilitated dissociation has also be seen in single-stranded DNA binding, 11 highlighting its widespread importance across all types of regulatory processes in cells.…”
mentioning
confidence: 99%